Induction of in Vitro Germination of Tandui (Mangifera rufocostata Kostrem.): Effect of Antioxidants and 2,4-dichlorophenoxyacetic Acid - Fitriani, Adistina; Arifin, Yudi Firmanul; Hatta, Gusti Muhammad; Wahdah, Raihani (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
The bark of tandui (Mangifera rufocostata Kostrem.) is commonly used as a medicine for diabetes. Regeneration of this plant is difficult, and continuous harvesting of the bark leads to a decrease in the plant population. The purpose of this research is to apply tissue culture techniques for the propagation of tandui. Different antioxidants (KNO3, polyvinylpyrrolidone (PVP), Murashige and Skoog (MS) media + PVP, and MS + ascorbic acid) and varying concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) (0.8, 1.0, 1.2, and 1.4 mg L–1) were tested for embryogenic tandui. The application of KNO3 and PVP suppressed the formation of browning in the media and explant of tandui. Soaking the explants in KNO3 and PVP reduce browning to 35% and 20%, respectively. The results also showed that increasing the concentration of 2,4-D enhanced the percentage of embryogenic tandui. Supplementing the media with 1.4 mg L–1 2,4-D resulted in 90% of embryogenic tandui. This study demonstrates that pre-soaking explants in antioxidants significantly reduces media browning, and supplementation of MS media with 2,4-D enhance embryogenic process. Thus, micropropagation of tandui could be achieved on a commercial basis.